(untitled) (The Pakistan Development Review, 1988)
A Philippine sample of agricultural households is studied by I subjective equilibrium model which also accounts for the household’s demographic structure. The model becomes a potent tool for integrating the economic and demographic behaviour of the household, since issues such as the value of children can be approached in a reality maximization framework and furthermore, such values call be causally rellted to the variance in measured fertility among different households (or Socioeconomic groups). For example, the low marginal productivity contribution of children in tenant (and small farm-size) households, along with the low fertility control that prevails there, has been combined In conforming the inverse fertility-endowments hypothesis, which in this instance is based on labour market failure in periods of peak agricultural labour demand. On the consumption side, on the other hand, the demand for leisure and for other commodities is consistent with the higher valuation of children, and thus higher fertility, in tenant (and small farm-size) households, as compared to owner (and large farm-size) households. The policy implications of such findings from a household equilibrium model are rich.